Peran Strategis Pajak Internasional dalam Mitigasi Base Erosion and Profit Shifting (BEPS) dan Dampaknya terhadap Pertumbuhan Ekonomi Berkelanjutan: Telaah Tantangan Implementasi di Negara Berkembang - Nila Ayu Kusuma Wardani; Luthfi Ariza Sahril Fadhilah (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2026)
The ongoing problem of Base Erosion and Profit Shifting (BEPS), which jeopardizes tax revenues and fiscal capacity in developing nations amid growing economic globalization, is the focus of this study. Examining the strategic role of international taxes in reducing BEPS practices and promoting sustainable economic growth is the primary goal of this study, with a focus on the implementation challenges that developing economies face. This study uses a qualitative descriptive approach to do an organized literature review of reliable sources, such as peer-reviewed academic papers, international tax agreements, and OECD reports. The approach combines actual data on tax avoidance, investment flows, and administrative capacity with theoretical viewpoints on tax justice. The findings show that multinational tax cooperation, especially through the multinational Instrument (MLI) and the OECD BEPS framework, has contributed to reducing aggressive tax planning and enhancing transparency. However, the effectiveness of these mechanisms in developing countries remains limited by structural challenges such as weak tax administration capacity, regulatory gaps, and competitive pressure to lower corporate tax rates. The study concludes that international taxation can function as a catalyst for sustainable economic growth only when global standards are integrated with strengthened domestic fiscal capacity and a more equitable allocation of taxing rights for developing countries.